Willingness to Pay to Overcome Pollution in Tapak River, Semarang - Susilowati, Indah; Malik, Hasmi Nurdinsyah; Afifah, Farah Aisha Nur; Niswah, Ulfatun; Choirunnisa, A’yuni (Universitas Negeri Semarang, 2019)
This study aims to analyze the level of Willingness to Pay of the community around TapakTugurejo Village, TuguSubdistrict, Semarang City in pollution prevention efforts on the Tapak River. This study offers a water purification model with the slow sands filtration method to improve water quality on the Tapak River. The analysis used was hypothetical market, Contingent Valuation Method (CVM), and multiple linear regression analysis to determine the Willingness to Pay relationship with other influencing factors, such as income, education, and age. Data was obtained from 30 respondents who were residents in RW04 TapakTugurejo Village, Semarang. Sample collection used in this study was the strategic random sample method. Hypothetical Market Value of respondents determines the willingness to pay for river pollution prevention efforts. The results found that the average cost of willingness to pay (WTP) of respondents for river pollution prevention activities from 30 respondents was Rp. 14,000.00. The total cost of WTP per year must be paid by the community from the loss of mangroves in the Tugurejo Village with a population of 6,941 people, was Rp 97,174,000.00.